PENGEMBANGAN BAHAN AJAR ILMU PENGETAHUAN ALAM DAN SOSIAL DENGAN PENDEKATAN HOTS (HIGHER ORDER THINKING SKILLS) MATERI SIKLUS AIR KELAS IV SD SWASTA PERGURUAN KEBANGSAAN MEDAN - Tasya Fatihah; Pangulu Abdul Karim; Abdul Gani Jamora (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to determine how smart monopoly develops in science learning for fourth grade students at Perguruan Kebangsaan Private Elementary School. This study is a research and development (R&D) study with a 4D development model, consisting of definition (definition), design (product design), development (development), and dissemination (dissemination). This study involved students who were in fourth grade at Perguruan Kebangsaan private school. Questionnaires, tests, student responses, and teacher responses were the research instruments. After collecting quantitative data, percentage techniques were used to analyze descriptive statistics. The results of the study include: 1) Making smart monopoly media for water cycle material. 2) The validity test of the card media (picture cards) obtained a score of 99% based on the c test, with a validity level of "very valid" based on the product validity criteria table by media experts, 73% based on the product validity criteria table by content/material experts, and 100% based on the c test, with a validity level of "very valid" based on the product validity criteria table by teachers. Thus, it can be concluded that the development of smart monopoly media in science learning for students in grade IV of elementary school/Islamic elementary school is very useful for use in the learning process.